Analyzing Systemic Failures in IT Incident Management: Insights from Post-Mortem Analysis - Faris Arifiansyah; Yuanita Handayati (Green Publisher Indonesia, 2025)
The reliability of IT systems is critical for fintech companies, where service disruptions can lead to significant financial losses and reputational damage. Despite established incident management frameworks, recurring IT incidents persist, indicating systemic weaknesses in prevention, detection, and response. This study aims to identify the root causes of significant IT incidents, assess detection and resolution challenges, and provide actionable recommendations to enhance incident management. Using a qualitative approach, the research analyzed 26 post-mortem reports from an Indonesian fintech company (August 2023–2024), employing thematic analysis to categorize systemic failures. Findings revealed that 80% of incidents stemmed from internal changes, primarily due to inadequate testing, weak deployment controls, and misconfigured production settings, while 69% lacked proactive alerts, delaying detection. Incident response inefficiencies, such as slow escalations and insufficient post-fix monitoring, further prolonged resolution times. The study highlights the need for stricter change validation, standardized alerting mechanisms, and automated deployment checks to mitigate disruptions. These insights offer practical guidance for fintech and technology companies to reduce incident frequency, improve detection capabilities, and optimize response efficiency. The research contributes to the broader IT incident management field by empirically validating failure patterns in fintech environments and proposing data-driven solutions. Future research could explore AI-driven automation and organizational factors influencing incident handling.